PERANAN FAKTOR-FAKTOR INTERAKSIONAL DALAM PERSPEKTIF TEORI SISTEM KELUARGA TERHADAP KESEJAHTERAAN KELUARGA - Dewi, Kartika Sari; Ginanjar, Adriana Soekandar (Jurnal Psikologi, 2019)
This study examined the role of interactional factors on family well-being, such as mother-child interaction, father involvement in parenting and perceived social support in the family. Respondents (N = 219) aged 17-35 years, completed an online survey assessment and answered open questions about family well-being. The results of the study show that the quality of parent-child interaction in the family is considered to play an important role in achieving family well-being, in addition to the perceived social support in the family. Family well-being is the results of the dynamics of interaction within the family which consists of cooperation, acceptance, trust, ritual, family vision and mission, also mutual love. Statistical calculations and theoretical discussions in the perspective of the Family System Theory (FST) are presented in full articles. The results of this study can be an early stage in exploring the parent-child interaction process and the extent of the role of media technology in family well-being in Indonesia.